Unraveling brain synchronisation dynamics by explainable neural networks using EEG signals. Application to dyslexia diagnosis - Gallego-Molina, Nicolás J.; Ortiz-García, Andrés; Arco, Juan E.; Martinez-Murcia, Francisco J.; Woo, Wai Lok (Springer, 2024)
The electrical activity of the neural processes involved in cognitive functions is captured in EEG signals, allowing the exploration of the integration and coordination of neuronal oscillations across multiple spatiotemporal scales. We have proposed a novel approach that combines the transformation of EEG signal into image sequences, considering cross-frequency phase synchronisation (CFS) dynamics involved in low-level auditory processing, with the development of a two-stage deep learning model for the detection of developmental dyslexia (DD). This deep learning model exploits spatial and temporal information preserved in the image sequences to find discriminative patterns of phase synchronisation over time achieving a balanced accuracy of up to 83%. This result supports the existence of differential brain synchronisation dynamics between typical and dyslexic seven-year-old readers. Furthermore, we have obtained interpretable representations using a novel feature mask to link the most relevant regions during classification with the cognitive processes attributed to normal reading and those corresponding to compensatory mechanisms found in dyslexia.
Keywords: Redes neuronales (Informática); Electroencefalografía; Dislexia; Brain synchronisation dynamics; Cross-frequency coupling; Dyslexia; Explainability